Elektron Mikroskopi dan Imunogenisitas Baculovirus oryctes Isolat Yogyakarta - Y. B. Sumardiyono (Universitas Gadjah Mada, 1995)
Palm rhinoceros beetle (Oryctes rhinoceros) was infected per os with Yogyakarta isolate of Baculovirus oryctes in laboratory condition. Midguts of infected beetle obtained were then extracted for further nucleoprotein purification by centrifugation method. Electron microscopy studies on purified nucleoprotein revealed rod-shape viruses with rounded end measured 190×94 nm in average. One end of the particle showed tail-like structure. Antibodies against the virus were obtained by immunization to rabbit, and reacted against either purified virus or extract of infected beetle, but not against extract of healthy beetle.